New officers´ education at the signal school. Reforms in education in terms of structure, content and costs with a main focus on National Crisis Management and Disaster Management - Treiblmaier Alexander (2017)
The education of soldiers in the Austrian armed forces is facing a radical change. Due to the current reform, the basic training of all soldiers is summarised and the following education has to be restructured. Against this background, the bachelor programme at the military academy has to be evaluat-ed and all changes in the requirements of an officer have to be integrated. During this evalu-ation, the whole structure of the bachelor programme has changed and the training of the officers at the signal school in Vienna has to be integrated in the study programme. This new sixth semester of the bachelor programme of the Austrian military academy limited to the education at the signal school is the major research gap filled in this thesis. To obtain a result, the current and new education systems are analysed and compared in the sectors of educational objectives and structure, duration and content and in the sector of the personnel and materials expenditure (costs). As a result, the necessary adaptions in the education curricula are also mentioned as the con-tents that have to be integrated into the postgraduate education. At the end, a fictive educa-tion structure including the positive aspects of both systems is presented. The research gap can be filled by the result that the educational level of the officers can largely be maintained and the new findings concerning which modules can remain nearly unchanged (basics of command support, electronic warfare, …) which modules have some limitations (all kinds of practical training) and which modules have to be taught after the promotion at the military academy (basics of data networks, basics of network security, …).